Predicting COVID-19 vaccination intentions with the Theory of Planned Behavior: a survey of healthcare workers - Brandt, Piper (Kansas State University, 2022)
Background: There has been a resurgence in vaccine hesitancy in recent years, possibly exacerbated by the increase in popularity of the internet and online media. This study examined the motivating factors behind healthcare workers’ (HCW) vaccine decisions and how media use may influence their decisions as well. Method: An online survey was distributed to American HCW (n=192) who worked in healthcare within the past two years. Measures were sourced from validated instruments and organized based on variables drawn from the Theory of Planned Behavior (TPB) constructs and media use. Data were analyzed using the Statistical Package for the Social Sciences software (SPSS). The reliability of the scales was determined by calculating Cronbach’s alpha. To test the research questions and hypotheses, descriptives of variables, Pearson correlation coefficient, one-way ANOVA, and independent samples t-test methods were performed. Results: Intention, measured among respondents who had not received any doses of the vaccine, was low overall (M=1.07, SD=.28). A Pearson’s correlation showed that social media use for news was significantly and positively correlated with intention (r=.291, p<.05). An independent samples t-test showed there was a significant difference in the scores for vaccine advice from media sources between the vaccinated and unvaccinated groups; t(171)=-6.33, p<.001. There was also a significant difference in the scores for vaccine information from other health professionals between the vaccinated and unvaccinated groups; t(169)=.9.89, p<.001. A one-way ANOVA showed there were significant differences in vaccine decisions between subjective norms [F (3, 169) = 30.97, p<.001] and attitudes [F (3, 160) = 82.67, p<.001]. Conclusion: The results concluded that unvaccinated HCW have negative attitudes about the COVID-19 vaccine, and are less trusting of the media, their social groups, and fellow HCW for advice about getting the vaccine. Unvaccinated HCW are a difficult demographic to target, so a better understanding of what motivates their decisions, and the decisions of those who have had at least some doses will prove to be useful in future health campaigns.
Keywords: Vaccination; Health communication; COVID-19